Safety of nuclear reactors part B: Unsteady-state strength mathematical model - El-Shayeb M.; Yusoff M.Z.; Bondok A.; Roseli A.; Ideris F.; Hassan S.H.A. (American Society of Mechanical Engineers, 2023)
The significant mechanical properties that determine the strength of concrete-filled square steel columns are compressive strength, modulus of elasticity, ultimate strain of the concrete, yield strength and modulus of elasticity of the steel. A survey of the literature shows that the variation of these properties with temperature is influenced by many factors. The compressive strength of concrete at elevated temperature is affected by the rate and duration of heating, the size and shape of the test specimen and the loading during the heating. During exposure to fire the strength of the column decreases with the duration of exposure. The strength of the column can be calculated by a method based on load-deflection analysis which in turn is based on a stress-strain analysis of cross-sections. A mathematical model describing the behavior of concrete-filled square steel column structures under load and heat has been thoroughly examined in this paper. The main goals of this model are to study the structure member characteristics (temperature, deformation and strength) under excessive heat conditions and to study the possibility of increasing the endurance time by changing the column composite structure.